Effects of chronic heart disease on skeletal muscle fiber size - Mattiello-Sverzut,A.C. (2005)
Size changes in muscle fibers of subjects with chronic heart disease (CHD) have been reported, although a consensus has not been achieved. The aims of the present study were to investigate a possible association between CHD and fiber size changes in the brachial biceps compared to subjects without heart disease. Forty-six muscle samples were obtained in autopsies of individuals (13 to 84 years) without neuromuscular disorders, 19 (10 males and 9 females) with, and 27 (14 males and 13 females) without CHD. In all cases muscle sections were stained with hematoxylin and eosin and processed for the visualization of myofibrillar ATPase activity. The lesser diameter of type 1 and type 2 fibers was obtained tracing their outlines (at least 150 fibers of each type per sample) onto an image analyzer connected to a computer. The results were analyzed statistically comparing males and females with and without CHD. Type 1 fiber mean lesser diameters were 51.51 and 54.52 µm in males (normal range 34-71 µm) and 45.65 and 55.42 µm in females (normal range 34-65 µm) without and with CHD, respectively; type 2 fibers measured 54.31, 58.23, 41.15, and 49.57 µm, respectively (normal range 36-79 µm for males and 32-59 µm for females). No significant difference in fiber size was detected in 24 males with and without CHD, while in 22 females there was a significant increase in size in those with cardiomyopathy. We concluded that CHD does not determine significant changes in fiber size. However, in females, there is some hypertrophy which, despite within normal range, may reflect morphologic heterogeneity of the sample, or the daily life activities in the upper limbs as a compensatory mechanism to fatigability that affect predominantly the lower limbs in subjects with CHD.